To solve the equation \( 3 - \frac{6}{5}x = -3 \), follow these steps:
-
Start by isolating the term with \( x \): \[ 3 - \frac{6}{5}x = -3 \] Subtract 3 from both sides: \[ -\frac{6}{5}x = -3 - 3 \] \[ -\frac{6}{5}x = -6 \]
-
Now eliminate the negative sign by multiplying both sides by -1: \[ \frac{6}{5}x = 6 \]
-
To isolate \( x \), multiply both sides by the reciprocal of \( \frac{6}{5} \), which is \( \frac{5}{6} \): \[ x = 6 \times \frac{5}{6} \] \[ x = 5 \]
Therefore, the solution is: \[ x = 5 \]